Central melanocortin receptors regulate insulin action - Obici, Silvana (American Society for Clinical Investigation, 2001)
Energy balance and insulin action are tightly coregulated. Leptin regulates energy intake and expenditure partly by modulation of the melanocortin pathway in the hypothalamus. Here we demonstrate potent effects of the melanocortin pathway on insulin action and body distribution of adiposity. Conscious rats received week-long infusions of either a melanocortin receptor agonist, α-melanocyte-stimulating hormone (α-MSH), or antagonist, SHU9119, in the third cerebral ventricle while food intake was maintained constant in each group. α-MSH decreased intra-abdominal fat and markedly enhanced the actions of insulin on both glucose uptake and production, while SHU9119 exerted opposite effects. Our findings elucidate a neuroendocrine network that is likely to play a central role in the coupling of energy intake and insulin action.